Use of controlled temperature chain and compact prefilled auto-disable devices to reach 2030 hepatitis B birth dose vaccination targets in LMICs: a modelling and cost-optimisation study. Issue 7 (July 2020) - Seaman, Christopher P; Morgan, Christopher; Howell, Jess; Xiao, Yinzong; Spearman, C Wendy; Sonderup, Mark; Lesi, Olufunmilayo; Andersson, Monique I; Hellard, Margaret E; Scott, Nick
Summary: Background: Hepatitis B causes more than 800 000 deaths globally each year. Perinatal infections are a major driver of this burden but can be prevented by vaccination within 24 h of birth. Currently, only 44% of newborn babies in low-income and middle-income countries (LMICs) receive a timely birth dose. We investigated the effects and cost-effectiveness of implementing ambient storage of hepatitis B vaccines under a controlled temperature chain (CTC) protocol and the use of compact prefilled auto-disable (CPAD) devices for community births. Methods: In this mathematical modelling study of perinatal hepatitis B transmission and disease progression, we estimated the coverage impact and cost-effectiveness of implementing CTC and CPAD interventions in the six Global Burden of Disease (GBD) regions containing LMICs. Combinations of four different scenarios of birth dose delivery strategies (cold chain, CTC) and interventions (needle and syringe, CPAD) were modelled across facility or community birth locations. We also estimated the minimum cost and most cost-effective strategy to achieve the WHO 90% hepatitis B birth dose coverage target in GBD regions and in 46 LMICs with a reported coverage of less than 90%. Findings: Current delivery protocols achieved a maximum coverage of 65% (IQR 64–65) across GBD regions. Reaching 90% hepatitis B birth dose coverage across all GBD regions was estimated to cost a minimum of US$687·5 million per annum ($494·0 million more than the estimated current expenditure), of which $516·5 million (75%) was required for CTC and CPAD interventions. Reaching 90% coverage in this way was estimated to be cost saving in five of the six regions (and in 40 of 46 LMICs individually assessed) due to the disease costs averted, with the cost per disability-adjusted life-years averted being less than $83·27 otherwise. Interpretation: Hepatitis B birth dose coverage of 90% is unlikely to be reached under current protocols. CTC and CPAD vaccine strategies present cost-effective solutions to overcome coverage barriers. Funding: The Burnet Institute.